The main treatments used for SARS-CoV-2 patients - Djamila, MERGHACHE (جامعة الوادي - University of Eloued, 2022)
As the COVID-19 pandemic continues to ravage the world and threaten people's lives, treating infected patients effectively has been one of the top concerns for medical workers around the world. Currently, no medication is recommended to treat COVID-19, and no cure is available. Researchers are testing a variety of possible treatments. Several drugs are being researched in different countries. Most are existing drugs that are being trialled against the virus. Pharmaceuticals undergoing clinical trials to assess their safety and efficacy as potential treatments for COVID-19, include the antiviral nucleotide analogue remdesivir, systemic interferons and in particular interferon β-1a, the antiviral combination lopinavir/ritonavir, the antimalarial chloroquine/hydroxychloroquine, and monoclonal antibodies against components of the immune system such as interleukin-6 (IL-6) and IL-4. It is important that the potential treatments are carefully assessed in randomised controlled trials.
article
Keywords: SARS-CoV 2, Antivirals, Immunomodulators, Corticosteroid therapy, Plasma therapy.